At the Crossroad of Cultures: Education and Identity of Hungarian Deaf Learners in Romania - Belényi, Emese (Central European Journal of Educational Research, 2019)
Deaf people living in ethnic-national minority situation form a social group whose members have multiple cultural backgrounds. Starting from interpretations which are viewing the deaf child as a member of a distinct cultural and linguistic minority, I studied the education of Hungarian deaf pupils in Romania graduating from the Hungarian Special School in Cluj/Kolozsvár/Klausenburg, with particular regard to the relationship between formal and informal language use in school, communication culture and identity. Methodologically the research is based on life path interviews with Hungarian Deaf Special School graduates, family case studies of two or three generation deaf families and structured interviews with experienced educators. The research results reveal that the educational practice of the concerned educational institution strengthens the pupils’ identity awareness and sense of belonging to the Hungarian nation in two distinct, still interconnected ways: on the one hand, through oral language acquisition, nursing the oral Hungarian language skills, and on the other hand through cultivating the Hungarian Sign Language embedded in the deaf culture within the learner community. Nowadays, the conditions and modalities of exercising this role are changing in several respects. The positive educational effects achieved so far can be reinforced and strengthened by educational policies based on the recognition and cultivation of cultural diversity, in all its complex and multifaceted manifestations, including the peculiar needs of ethnic minority deaf learners.